The Influence Of Work Environment And Work Motivation On Employee Performance PDAM Toraja Utara - Dianti Rantelain; Adriana Madya Marampa; Rahma G. Tammu (UNIVED Press, 2023)
This study aims to determine the effect of the work environment and work motivation on the performance of PDAM Toraja Utara employees. The sampling technique in this study used a simple random sampling method, the data collection technique used a questionnaire. The data analysis technique used in this study is the quantitative method using multiple linear regression analysis, classical assumption test, f test, t test and the coefficient of determination. The results of the research show that there is an influence of the independent variables of work environment and work motivation on the dependent variable of employee performance. This can be seen through the f test by obtaining a significance value for the effect of X1 and X2 on Y of 0.000. This significance value is less than 0.05, when compared with the calculated F value with F table, it is obtained 47.238 > 3.18, so it can be concluded that there is an influence of the work environment and work motivation on the performance of North Toraja PDAM employees. The influence of the work environment and work motivation on employee performance is 65%